(untitled) (Journal of Global Accounting, 2023)
This study examined the effect of abnormal discretionary expenses on financial performance of listed manufacturing firms in Nigeria for a period of ten (10) years covering from 2013-2022. Sudden collapse of companies that once appeared viable and futuristic is a serious concern. Panel data were used in this study, which were obtained from the annual reports and accounts of twenty (21) sampled listed manufacturing firms for the period 2013-2022. Ex-Post Facto research design was employed. Inferential statistics using Pearson correlation coefficient, Multicollinearity test, Panel Least Square (PLS) regression analysis and Hausman test were applied to test the hypotheses of the study. The results revealed that abnormal corporate social responsibility cost has a significant and positive effect on cash value added (β3=0.011970; p-value = 0.0088); abnormal employee benefit has a significant but negative effect on cash value added (β4=-0.036034; p-value = 0.0010) of listed manufacturing firms in Nigeria at 5% level of significance respectively. In conclusion, the study found that abnormal discretionary expenses has a significant effect on financial performance of listed manufacturing firms at 5% level of significance. The study recommended amongst others that firms should discretionally utilize both ACSRC and EAB to improve and sustain performance.